The Effect of Smoking Hazards Slogan Listed on Cigarette Packs on Purchase Interest - Ihwanul Muslimin; Intisari Haryanti (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2021)
Cigarettes are rolled or rolled tobacco that is rolled/ wrapped in the paper either by hand or by machine. Cigarettes are also an addictive substance which when used can cause health hazards for individuals and society. The health slogans on the dangers of cigarettes on the cover of cigarette packs are scary, like pictures of a perforated throat or heart disease, but people still have an interest in buying and care less about stopping smoking. The purpose of this study was to determine the effect of the Dangers of Smoking Slogans on Cigarette Packs on Buying Interest in the City of Bima. The population used is all people in the city of Bima who consume cigarettes whose number is not known with certainty with a sample size of 96 respondents. The population used is all people in Bima City who consume cigarettes that are not known for certain. while the number of samples is as many as 96 people with techniques based on criteria or purposive techniques. Then analyzed the data with a simple linear regression technique. Based on the data analysis that has been done, it can be concluded that the slogan of the dangers of smoking listed on cigarette packs has no significant effect on people's purchase interest in Bima City.